Determination of insect population in rice paddy cultivation by using selected traps / Noor Ibrahim Mohd Rashidi - Mohd Rashidi, Noor Ibrahim (Faculty of Plantation and Agrotechnology, 2018)
The class Insecta, or insects, are the Arthropod that has three pairs of legs, a segmented body divided into three regions, one pair of antennae and, usually, wings. In this world, insect is the most populated living thing that can be found in any parts of this world. Oryza sativa, or commonly called is rice paddy is one of the crop cultivation, that is very important in world food diet for humankind. It about half of the world population taking rice as their staple food, especially in Asia and South America. The relationship between insect and rice paddy is rice paddy field is one of the nature for the insects to live in. in fact, paddy and insect is a great symbiosis for each other because they keeping the balance for each other. In this study, determination of the insect by sampling method is done to calculate their population in an certain area. The insects population is collected by using certain selected traps, where conventionally used by the researchers and farmers. A rice cultivation field was chosen to further this study, which is plotted in south Peninsular Malaysia, in Melaka state, Merlimau. The study had been held about five consecutive weeks, by using three types of traps with four replications for each trap. The research then sum up with conclusion for each objective where Modified Light-Stick Trap was the most effective trap from three traps selected, and the most dominant insect’s order was Hymenoptera. The results of each collection are depending on the climate condition and control activities by the paddy field owner by the time of research.